Flexible Electrodes: Paper‐Based Electrodes for Flexible Energy Storage Devices (Adv. Sci. 7/2017). Issue 7 (18th July 2017) - Yao, Bin; Zhang, Jing; Kou, Tianyi; Song, Yu; Liu, Tianyu; Li, Yat
Abstract : Assembly of electrochemically active materials into paper‐based electrodes opens up new opportunities for flexible energy storage devices. Yat Li and co‐workers review the recent advances in the synthesis of paper‐based electrodes, including paper‐supported electrodes and paper‐like electrodes in article1700107 . Their structural features, electrochemical performances and implementationas electrodes for flexible energy storage devices are highlighted and discussed.